Modification of surface glycan by expression of beta-1,4-N-acetyl-galactosaminyltransferase (B4GALNT2) confers resistance to multiple viruses infection in chicken fibroblast cell - Park, Jin Se; Woo, Seung Je; Song, Chang Seon; Han, Jae Yong (Frontiers in Veterinary Science, 2023)
Infectious viruses in poultry, such as avian influenza virus (AIV) and Newcastle disease virus (NDV), are one of the most major threats to the poultry industry, resulting in enormous economic losses. AIVs and NDVs preferentially recognize α-2,3-linked sialic acid to bind to target cells. The human beta-1,4-N-acetyl-galactosaminyltransferase 2 (B4GALNT2) modifies α-2,3-linked sialic acid-containing glycan by transferring N-acetylgalactosamine to the sub-terminal galactose of the glycan, thus playing a pivotal role in preventing viruses from binding to cell surfaces. However, chickens lack a homolog of the B4GALNT2 gene. Here, we precisely tagged the human B4GALNT2 gene downstream of the chicken GAPDH so that the engineered cells constitutively express the human B4GALNT2. We validated human B4GALNT2 successfully modified α-2,3-linked sialic acid-containing glycan in chicken DF-1 cells via lectin binding assay. In addition, we showed that human B4GALNT2 reduced infection of two AIV subtypes and NDV. Collectively, these results suggest that artificially expressing human B4GALNT2 in chicken is a promising strategy to acquire broad resistance against infectious viruses with a preference for α-2,3-linked sialic acids such as AIV and NDV.